Polo-like kinase 1 as a potential therapeutic target and prognostic factor for various human malignancies: A systematic review and meta-analysis - Wang, Ming-Wen; Li, Zhong; Chen, Li-Hong; Wang, Ning; Hu, Jian-Ming; Du, Jin; Pang, Li-Juan; Qi, Yan (Frontiers in Oncology, 2022)
Abstract Objective: The overexpression of polo-like kinase 1 (PLK-1) has been found in a broad spectrum of human tumors, which is an attractive prognostic tumor biomarker, nowadays PLK1 is considered as a potentially valuable therapeutic target for cancer. The present study was to undertaken to systematically review the prognostic and therapeutic value of PLK-1 in different malignant neoplasms. Methods: A systematic literature search of Cochrane Library, PubMed, Web of Science, the China National Knowledge Internet (CNKI) was conducted from December 2018 to October 2019. In total, 36 published studies were screened, including 4697 cases. In this study, we calculated pooled odds ratios (ORs) and corresponding 95% confidence intervals (CIs) for clinical parameters of cancer patients and pooled hazard ratios (HRs) and corresponding 95% CIs for five-year overall survival (OS). Results: This meta-analysis enrolled 36 eligible studies with a total of 4697 patients. The results showed that overexpression of PLK-1 was significantly associated with poor OS (HR, 1.57; 95%CI, 1.18-2.08), and inferior to 5-year DFS/RFS (HR, 1.89; 95%CI, 1.47-2.44). The pooled analysis showed that PLK-1 overexpression was significantly associated with lymph node metastasis, histological grade, clinical stages(P<0.0001，respectively), tumor grade (P=0.010). In digestive system neoplasms, PLK-1 overexpression was significantly associated with histopathological classification, primary tumor grade,histological grade, tumor grade lymph node metastasis and clinical stages (P =0.028，P =0.013，P<0.0001，P=0.001, respectively). In breast cancer, PLK-1 was significantly associated with five-year overall survival, histological grade and lymph node metastasis (P<0.0001, P =0.004, P<0.0001, respectively). In female reproductive system, PLK-1 was significantly associated with clinical stages (P =0.011). In respiratory system, PLK-1 was significantly associated with clinical stages (P=0.021). Conclusion: Our analysis indicates that high PLK-1 expression is associated with aggressiveness and poor prognosis in malignant neoplasms, PLK1 may be a clinically valuable target for cancer treatment.